Exploring the role of the patient–physician relationship on insulin adherence and clinical outcomes in type 2 diabetes: Insights from the MOSAIc study†: 在2型糖尿病患者中调查患者‐医生关系对胰岛素依从性以及临床结局的影响:MOSAIc研究见解. (17th August 2016) - Linetzky, Bruno; Jiang, Dingfeng; Funnell, Martha M.; Curtis, Bradley H.; Polonsky, William H.
Abstract: Background: The 2‐year prospective MOSAIc (Multinational Observational Study assessing Insulin use: understanding the challenges associated with progression of therapy) study is investigating whether patient‐, physician‐, and health system‐related factors affect outcomes in patients with type 2 diabetes (T2D). This baseline subanalysis investigated how aspects of the patient–physician relationship are associated with diabetes‐related distress, insulin adherence, and glycemic control. Methods: Patients with T2D taking insulin for ≥3 months were recruited at primary care and specialty practice sites in 18 countries. Physicians provided usual care. Clinical history and most recent HbA1c values were collected; patients were surveyed regarding their perception of physician interactions, diabetes‐related distress level, and insulin adherence. Results: The analysis population comprised 4341 patients. Four (of six) domains showed a significant relationship with total diabetes‐related distress ( P  < 0.01). Poor insulin adherence was associated with greater diabetes‐related distress (adjusted odds ratio [aOR] 1.14; 95% confidence interval [CI] 1.06–1.22), higher Discrimination (aOR 1.13; 95% CI 1.02–1.27) and Hurried Communication (aOR 1.35; 95% CI 1.20–1.53) scores, and a lower Explained Results score (aOR 0.86; 95% CI 0.77–0.97). Poor insulin adherence was associated with a 0.43% increase in HbA1c, whereas a 1‐unit increase in total diabetes‐related distress and Hurried Communication scores was associated with a 0.171% and 0.145% increase in HbA1c, respectively. Conclusions: Patients distressed about living with T2D, and dissatisfied with aspects of their interactions with physicians, exhibited poor insulin adherence. Perceived physician inattention and lack of engagement (and diabetes‐related distress) directly affect insulin adherence and glycemic control. Highlights: Patient perceptions of the quality of their interactions with their physicians have a significant association with total diabetes‐related distress. Diabetes‐related distress and patient–physician interactions have a significant independent association with insulin adherence and HbA1c level. This study delineates specific aspects of the patient–physician interaction that are linked to diabetes‐related distress, insulin adherence behavior, and glycemic control. Path analysis showing associations between patient–physician interactions, diabetes‐related distress, insulin adherence, and HbA1c level. The model is not adjusted for baseline covariates and shows only those factors with at least one significant interaction. Parameter coefficients in the path analysis are shown.